Isolation and Characterisation of CDNA Clones Encoding Adp-Glucose Pyrophosphorylase (AGP) from Sago Palm (Metroxylon Sagu) - Au, Sian Loong (2001)
In general, the biosynthetic steps required for starch biosynthesis involves three major enzymes: ADP-glucose pyrophosphorylase (AGP), starch synthase (SS) and starch branching enzyme (SBE). Many studies have indicated that AGP is an important control point of flux through the pathway of starch biosynthesis in many plant species. All plant AGPs are composed of two subunit types, large (lAGP) and small (sAGP) subunits that give rise to an U2(:l2 heterotetrameric native enzyme. The presence of both subunits are crucial for the stability and activity of the enzyme. One full length and three partial AGP cDNA clones have been isolated and clBracterised from sago palm leaves and pith by a PCR amplification technique. Three of the clones (agp1l9, agpp10 and agpp12) encode AGP large subunits; the fourth clone (agpll) encodes a small subunit. The complete cDNA of agpl2· has been isolated from a mature leaf cDNA library by a PCR screening technique. Semi-quantitative RT-PCR analysis revealed that agpl19 was leaf specific while agppl0 and agpp12 were pith specific. agpll was found to be present in leaves as well as pith tissue.